Weill- Marchesani Syndrome: a rare case report - Puri, L R; Sharma, H; Aryal, S (Nepalese Journal of Ophthalmology, 2012)
Objective: To describe the presenting features of Weill-Marchesani syndrome Case: A 22-year-old man presented with high myopia and progressive visual disturbance. He was of short stature and had brachydactyly. His initial Snellen best corrected visual acuity (BCVA) was 6/24 in his right eye and 6/12 in his left eye. Slit lamp examination revealed a sub-luxated micro-spherophakic lens. The patient was diagnosed with Weill-Marchesani syndrome. Conclusion: Weill-Marchesani syndrome can present wwith progressive myopia in a person of short stature and brachydactyly. DOI: http://dx.doi.org/10.3126/nepjoph.v4i2.6558 Nepal J Ophthalmol 2012; 4 (2): 336-338